Population Abundance, Distribution, Forecasting Models And Breeding Habitat Ecology Of Dengue Vectors In Penang Island - Hashim, Nur Aida (2013)
Ovitrap study was carried out to determine the field population abundance of dengue vectors, Aedes albopictus (Skuse) and Aedes aegypti (Linnaeus) in three dengue hotspots in Penang Island from February 2008 to March 2010 (108 weeks). Thirty ovitraps were placed in each study area and collected weekly. The urban squatter area (Sungai Nibong Kecil) had the highest total number of eggs and immatures throughout the sampling period, followed by urban area (Sungai Dua) and suburban area (Permatang Damar Laut). The amount of eggs collected were higher in wet season compared to dry season. The egg population showed a significant correlation with rainfall and relative humidity but not with mean temperature. Fogging activities were effectively reduced Aedes population during dry season as compared to wet season. An autoregressive integrated moving average (ARIMA) model was applied to the ovitraps data set from the three study sites. The models estimated were judged to both fit and forecast with sufficient accuracy to warrant their use in strategic Aedes control. The ARIMA (1,0,0), ARIMA (2,0,0) and ARIMA (0,1,1) models were judged to best fit the suburban area, urban squatter area and urban area data sets respectively.